2021
DOI: 10.3390/jcm10153283
|View full text |Cite
|
Sign up to set email alerts
|

Electric Scooter-Related Injuries: A New Epidemic in Orthopedics

Abstract: Background: The use of electric scooters has increased considerably as they are an accessible means of transportation. The number of injuries from falls and collisions has risen significantly. Therefore, the aim of the study was to describe demographics injury patterns of electric scooter accidents produced over one year. Methods: A prospective observational study of electric scooter- related injuries presented in the emergency room from May 2019 until May 2020. The inclusion criteria was based on the direct c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
27
3
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 32 publications
9
27
3
8
Order By: Relevance
“…Both e-scooter and bicycle riders were mostly male young adults and the proportion of older adults (≥ 65 years) among e-scooter riders was ten times lower than bicycle riders. This is consistent with that reported elsewhere [ 13 , 18 , 19 ] and reflects both the urban implementation of e-scooter sharing companies and their target customers’ profile. More interestingly, we found that a moving car was less frequently involved in e-scooter crashes compared to cycling incidents, which has also been reported by Cicchino et al .…”
Section: Discussionsupporting
confidence: 92%
“…Both e-scooter and bicycle riders were mostly male young adults and the proportion of older adults (≥ 65 years) among e-scooter riders was ten times lower than bicycle riders. This is consistent with that reported elsewhere [ 13 , 18 , 19 ] and reflects both the urban implementation of e-scooter sharing companies and their target customers’ profile. More interestingly, we found that a moving car was less frequently involved in e-scooter crashes compared to cycling incidents, which has also been reported by Cicchino et al .…”
Section: Discussionsupporting
confidence: 92%
“…There were six cases of extremity fractures in our study, and three (50%) were operated on. This was consistent with an article by Coelho et al [18] reporting the need for surgery in more than 50% of extremity fractures in e-scooter accidents.…”
Section: A a B Bsupporting
confidence: 92%
“…A idade média situa-se entre os 30.8-35.4 anos, com 11% a apresentar idades inferiores a 16 anos e mais de 50% a situar-se na faixa etária dos 30 aos 60 anos. 1 Verifica-se um predomínio de ocorrência de acidentes no sexo masculino (50-76%) e nos meses de Verão (figura 3) entre as 15h e as 23h dos dias úteis, que apresenta uma variação significativa para o período da noite ao fim de semana, em provável relação com o divertimento noturno.…”
Section: Traumatologia Associada àS Trotinetas Elétricasunclassified
“…A educação dos condutores representa outro foco potencial de atuação, uma vez que 45% das vítimas não tem carta de condução e não existe a obrigatoriedade de qualquer formação ou treino para a condução das trotinetas elétricas. 1…”
Section: Traumatologia Associada àS Trotinetas Elétricasunclassified
See 1 more Smart Citation